Proceedings of the 32st ACM Conference on Hypertext and Social Media 2021
DOI: 10.1145/3465336.3475110
|View full text |Cite
|
Sign up to set email alerts
|

Structack: Structure-based Adversarial Attacks on Graph Neural Networks

Abstract: Recent work has shown that graph neural networks (GNNs) are vulnerable to adversarial attacks on graph data. Common attack approaches are typically informed, i.e. they have access to information about node attributes such as labels and feature vectors. In this work, we study adversarial attacks that are uninformed, where an attacker only has access to the graph structure, but no information about node attributes. Here the attacker aims to exploit structural knowledge and assumptions, which GNN models make abou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Additionally, we found that connecting two nodes with low node centrality (in terms of degree and PageRank centrality) is also an effective attack. This demonstrates that low-degree attacks [42,43], which are effective in static graphs, also exhibit partial effectiveness in dynamic graphs.…”
Section: Attack Performancementioning
confidence: 85%
“…Additionally, we found that connecting two nodes with low node centrality (in terms of degree and PageRank centrality) is also an effective attack. This demonstrates that low-degree attacks [42,43], which are effective in static graphs, also exhibit partial effectiveness in dynamic graphs.…”
Section: Attack Performancementioning
confidence: 85%
“…As the perturbations generated by our attack are the least likely edges to be formed when considering the graphs' dynamics, these perturbations effectively Additionally, we found that connecting two nodes with low node centrality (in terms of degree and PageRank centrality) is also an effective attack. This demonstrates that low-degree attacks (Hussain et al 2021;Ma, Ding, and Mei 2020), which are effective in static graphs, also exhibit partial effectiveness in dynamic graphs.…”
Section: Attack Performancementioning
confidence: 88%
“…Topology Attacks. With the wide applications of GNNs, their robustness to adversarial attacks has received increasing attention, especially for topology attacks [5,7,9,11,21,22,29,33,38,39,42,42,47]. They try to find the most adversarial perturbations within a fixed budget Δ.…”
Section: Related Workmentioning
confidence: 99%